PENGARUH LINGKUNGAN PENDIDIKAN DALAM MENGEMBANGKAN WIRAUSAHA MUDA DI STIE GANESHA - Ramadhanna, Ramadhanna; Sari, Yuniva; Ramadhinna, Ramadhinna; Safitri, Desy Yana; Siswanto, Arik; Saefullah, Aep; Siregar, Fuad Gagarin (Jurnal Ekonomi Sakti, 2024)
The purpose of this study is to determine the influence of the educational environment in developing entrepreneurship of STIE Ganesha students. The study was conducted for 2 months in October and November 2023 to 30 students of STIE Ganesha. The method used is descriptive qualitative. Data were collected through literature studies, interviews, and observations. The results show that the campus environment can foster an entrepreneurial spirit among students. The role of institutions and lecturers is important in fostering the interest of students' entrepreneurial talents. Ganesha Lab Prenuer as an entrepreneurship center institution also plays a role in increasing student entrepreneurship generation. The strategies carried out by the campus are in the form of guidance and mentoring inside and outside the classroom, student mapping, entrepreneurial skills and formalization of the entrepreneurial student community.